Efficacy of Thiodicarb, Cadusafos and soil conditioner via seed and/or planting furrow treatment for Pratylenchus brachyurus control in soybean crops. Summa Phytopathologica - Guarnieri, Carlos Cesar de Oliveira [UNESP]; Souza, Gabriel Baroni Costa [UNESP]; Soares, Pedro Luiz Martins [UNESP] (FapUNIFESP (SciELO), 2025)
Various factors directly or indirectly affect soybean productivity, especially parasitism by the root lesion nematodes Pratylenchus brachyurus, which causes significant losses in different producing regions. The present study aimed to evaluate the efficiency of various chemical treatments applied to the seeds and/ or in the planting furrow of soybeans, in naturally infested areas, and in pots containing soil infested with Pratylenchus brachyurus. Applications to the seeds and in the planting furrow were tested with Thiodicarb, as well as Cadusafos and a soil conditioner. It was concluded that seed and furrow treatments did not cause visual symptoms of intoxication in the crop. The use of furrow treatment in addition to seed treatment increased crop productivity, depending on the used products. Individually, seed treatment with Thiodicarb was as effective in reducing the total population of Pratylenchus brachyurus in soybean roots as furrow treatment with Cadusafos or Cadusafos + Maskio. Furrow treatment with Thiodicarb, in addition to seed treatment with the same product, was effective in controlling root lesion nematodes in the pot trial, increasing soybean productivity by more than nine bags per hectare in areas naturally infested with the nematode.
Eficácia de tiodicarbe, cadusafós e condicionador de solo via tratamento de sementes e/ ou sulco de plantio no controle de Pratylenchus brachyurus na cultura de soja
Keywords: chemical control; Glycine max; root lesion nematode